2008
DOI: 10.1111/j.1440-1843.2007.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleural fluid interleukin‐8 and C‐reactive protein for discriminating complicated non‐purulent from uncomplicated parapneumonic effusions

Abstract: Pleural fluid IL-8 is an accurate marker for the identification of non-purulent CPPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
3
19
0
1
Order By: Relevance
“…Indeed, a number of studies provide support for the use of CRP as a diagnostic aid in tuberculous pleuritis; low pleural CRP levels (,30 mg?L -1 ) make this diagnosis unlikely while being more indicative of a malignancy in patients with exudates [8][9][10]. In addition, our findings complement the scarce previous literature on the application of CRP for identifying CPPE [11,12]. This biomarker emerged as an independent predictor of nonpurulent CPPE in the multivariate analysis, although its adjusted LR+ was lower than those for glucose and LBP.…”
Section: Discriminating Ppe From Other Aetiologiessupporting
confidence: 70%
“…Indeed, a number of studies provide support for the use of CRP as a diagnostic aid in tuberculous pleuritis; low pleural CRP levels (,30 mg?L -1 ) make this diagnosis unlikely while being more indicative of a malignancy in patients with exudates [8][9][10]. In addition, our findings complement the scarce previous literature on the application of CRP for identifying CPPE [11,12]. This biomarker emerged as an independent predictor of nonpurulent CPPE in the multivariate analysis, although its adjusted LR+ was lower than those for glucose and LBP.…”
Section: Discriminating Ppe From Other Aetiologiessupporting
confidence: 70%
“…In a logistic regression analysis [17] that included classical pleural fluid biochemistries, TNFa at a cutoff of 80 pg/ml was the most useful diagnostic indicator for CPPE (adjusted likelihood ratios þ 7.6). Likewise, in a comparative study [18] between UPPP and CPPE, pleural fluid levels of IL-8 exhibited good discriminative properties (AUC 0.87).…”
Section: Proinflammatory Cytokinesmentioning
confidence: 90%
“…The increasing numbers of inflammatory cells within the pleural space lead to a rise in lactate dehydrogenase [77], often in excess of three times the upper limit of normal. A recent report has demonstrated that pleural fluid IL-8 can be an accurate discriminator of complicated and uncomplicated parapneumonic effusion [78], although the same report also demonstrated that pleural fluid pH was equivalent to IL-8 in such discrimination. As a result, pH remains the most useful in defining the need for pleural drainage [14,79].…”
Section: Thoracocentesismentioning
confidence: 97%